PEMBELAJARAN PROYEK MATA PELAJARAN FISIKA DI SMA SEBAGAI STARTING POINT PEMBENTUKAN BUDAYA MENELITI - Jarwanto, Agus (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2012)
Physics is the science that is not easy for most students. Interesting learning physics is increasingly tried. The constructive method in learning helps for the development of the cooperative learning. The project learning is one of the learning models, which has the freedom from the constraint. The initiation needs some supporting factors. This learning has strengthens and weakness. It has been found the positive results from the learning, namely the main value. The project learning becomes a starting point to run research. The view of teachers is increasing through the project learning, Keywords: Constructive, project leraning, research culture.